VD_FINDINFO HC / 2012 / 178 vom 23. Februar 2012 - VD Tribunal cantonal (2012)
CHOSE JUGÉE, DÉCISION INCIDENTE, EXCEPTIONMOYEN DE DÉFENSE | 142 al. 1 CPC, 142 CPC, 475 al. 1 CPC, 475 al. 2 CPC, 475 CPC